Continuously tunable narrowband pulses in the THz gap from laser-modulated electron bunches in a storage ring - P. Ungelenk; M. Höner; H. Huck; S. Khan; C. Mai; A. Meyer auf der Heide; C. Evain; C. Szwaj; S. Bielawski (Physical Review Accelerators and Beams, 2017)
This article reports on the generation of narrowband coherent synchrotron radiation from an electron storage ring. For the first time, this kind of radiation was now produced with continuously tunable frequencies in the so-called “THz gap” (between 1.2 and 5.6 THz), whereas previous experiments were limited to below 750 GHz. The experiment was performed at the DELTA storage ring in Dortmund, Germany, employing the interaction of external intensity-modulated laser pulses with an electron bunch, which causes a periodic longitudinal modulation of the charge density on a sub-millimeter scale. Furthermore, a strong influence of third-order dispersion in the laser pulses on the bandwidth and peak intensity of the THz radiation was observed. This effect is discussed in detail based on numerical simulations of the laser pulse generation and laser-electron interaction, and a modification of the laser system for compensating third-order dispersion is proposed.